Adapted physical activity and cardiac coherence in hematologic patients (APACCHE): study protocol for a randomized controlled trial - Claire Fournié; Nicolas Bouscaren; Georges Dalleau; Victorine Lenclume; Catherine Mohr; Patricia Zunic; Quentin Cabrera; Chantal Verkindt (BMC, 2020)
Abstract Background Hematologic malignancies and their treatments are recognized for their significant long-term adverse effects on health-related quality of life. As a part of cancer treatment, physical exercise is known to improve physical functioning, but there are still questions regarding its impact on psychological and emotional functioning. Nonetheless, heart rate variability biofeedback (HRVB) is recognized for its positive effects on autonomic nervous system balance and emotional self-regulation. The Adapted Physical Activity and Cardiac Coherence in Hematologic Patients (APACCHE) protocol is a randomized, controlled superiority trial designed to evaluate the effects of HRBV training combined with an adaptive physical activity (APA) program compared to APA alone on the post-treatment quality of life of adult hematologic patients. Methods Seventy patients aged 18-70 years, with various forms of hematological malignancies, in post-treatment remission within six months prior to beginning the study and who have been prescribed APA by a hematologist, will be randomly allocated in a 1:1 ratio to two 12-week treatment groups: HRVB + APA versus APA alone. APA sessions will consist of aerobic and resistance training for 1-h twice weekly. The HRVB training will consist of controlled breathing exercises with biofeedback of heart rate variability for 10 sessions and will include a daily home-based practice. The primary outcome will be to evaluate health-related quality of life (QLQ-C30, SF-36). The secondary outcomes will be to evaluate fatigue (MFI-20); anxiety and depression (HADS); clinical status with blood pressure, progression-free survival, overall survival, and body mass index; heart rate variability level and cardiac coherence score. All of these assessments will be evaluated initially (T1), 6 weeks after (T2), at the end of the 12 weeks (T3), and then at a 12-week post-intervention follow-up (T4). Discussion To our knowledge, this is the first protocol to investigate the additional value of HRVB on physical exercise. In addition, there has been no study previously published about HRVB in hematologic patients. We hypothesize that overall quality of life and psychological and physical functioning will be improved, potentially offering a better understanding of supportive cancer care in hematology and inferring new perspectives in psychophysiological research in cancer. Trial registration Current randomized controlled trial was registered 29 November 2017 on Clinical Trials.gov (NCT number: NCT03356171 ).